Web GIS Based Benthic Habitat Mapping Update Supports Smart Island Lemukutan - Zibar, Zan; Saputra, Robin; Raynaldo, Adityo; Supriyatno, Supriyatno (Politeknik Negeri Batam, 2024)
Benthic habitats are important for the quality of life and global climate. Systematic and efficient information is important for the monitoring, mapping, and recording of aquatic bottom habitats, thus providing a habitat database. In the last decade, object-based image analysis (OBIA) has been accepted as an effective method for extracting and classifying information from high spatial resolution satellite imagery. Our study's goal is to use WebGIS to combine coral reef monitoring data from Lemukutan Island and find out how much coral cover there is on the island using the smart island WebGIS. This study took place from August 6th to August 13th, 2024, and used a total of 1097 field points to show where all the benthic habitats and Sentinel 2A image data sources were located. The research results obtained the extent of shallow water benthic habitat classification with different variations in each habitat class. The Rock Class covers an area of